PENERAPAN SOMATIC AUDITORY VISUAL INTELLECTUAL UNTUK MENINGKATKAN HASIL BELAJAR KALOR DI SMP - Alfena, Nuriski; Djudin, Tomo; Hamdani, Hamdani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThis research aimed to test the effectiveness of Somatic Auditory Visual Intellectual (SAVI) model to improve students learning result about heat in SMP N 22 Pontianak. The method of this research was quasi experimental nonequivalent control group. The samples of this research were all VII A students as experimental class and VII C students as control class that were selected through intact group technique. The instrument that was used consisted of 8 objective questions and 3 essai questions. The results of this research were: (1) The participants of the experiment class have improvement on the results of the study 31.17, higher compared with the control class of 17.58 . (2) There are differences of the study results from participant of experiment class and control class (.Sig 0.012<0.05] after the learning activities. (3) The SAVI learning effectiveness is 0.73 (category is moderate) in improving the study results of the participant compared to conventional learning. The implementation of Somatic Auditory Visual Intellectual (SAVI) is expected to become an alternative in improving the results of the study from the participants on other physics teaching and learning materials.Keywords: Heat, Results study, Somatic Auditory Visual Intellectual